Nonnative Fish to Control Aedes Mosquitoes: A Controversial, Harmful Tool - Azevedo-Santos, Valter M. [UNESP]; Vitule, Jean R. S.; Pelicice, Fernando M.; Garcia-Berthou, Emili; Simberloff, Daniel (Oxford Univ Press, 2017)
Zika, chikungunya, yellow fever, and dengue are mainly transmitted to humans through Aedes mosquitoes. In attempts to control these diseases, governments and the public have encouraged the use of fish predators to control mosquito populations. However, the efficacy of using these predators for mosquito-population control is largely unproven and dubious, particularly for container-breeding mosquitoes that reproduce in minute aquatic habitats, which are unsuitable for fish. Moreover, the use of nonnative fish for biological control entails a high potential risk of promoting escapes and invasions, which can impair ecosystem functioning and biodiversity. Although this risk is recognized, the practice may intensify in countries affected by recent epidemics transmitted by Aedes spp. Therefore, we argue that the use of nonnative fishes to control Aedes mosquitoes is ungrounded and ecologically damaging and point out that other approaches (e.g., habitat management, biotechnological tools, and more evidence-based integrated management) should be used to combat mosquito-borne human diseases.
Keywords: Zika; public health; invasive species; mosquito control; Aedes aegypti